The effect of online classes toward student’s motivation / Ahmad Abdul Mukmin Abd Rahman and Muhammad Taufiq Yiddin - Abd Rahman, Ahmad Abdul Mukmin; Yiddin, Muhammad Taufiq (2022)
There are lot of effect of online classes especially towards student’s motivation in terms of health, academic achievement and cost. The main objective of this research is to study the relationship between the health, academic achievement and cost towards student’s motivation together with the main determinant of student’s motivation. A sample of 360 respondents of UiTM Negeri Sembilan, Kampus Seremban 3 students were provided with a set of questionnaires in order to collect primary data. The analysis of the data that have been used are Pearson Correlations, Multiple Regression and Descriptive Statistics in order to study the independent variables which is health, academic achievement and cost. Based on the research done, the level of awareness on the effect of online classes is high and the independent variables have such positive significant relationship with the dependent variable. From the finding, it shows that the highest variation that contributed to the student’s motivation is health. The summary of the research findings, research recommendations and research limitations and research suggestions and limitations are being explained further in the study.